Gaya Hidup Masyarakat Modern: Perilaku Konsumtif Remaja di Mal Podomoro Medan - Muhammad Fajar Syaban Lubis; Muhammad Kabul; M. Anas Azhar Rambe; Lukitaningsih; Tara Ashiilah (IAI Nasional Laa Roiba Bogor, 2024)
This study investigates teenagers’ consumptive behavior in purchasing shoes at Podomoro Mal Medan. Through a qualitative approach with a case study design, data was collected through interviews with a teenage shoe collection enthusiast and a shoe seller at the Reebok store in the mal. The interview results revealed that the main motivations for purchasing shoes by teenagers are to increase self-confidence and fulfill social needs in a peer environment. Peer influence and fashion trends also influence teenagers’ shoe purchasing patterns. In addition, the existence of shopping centers that offer various brands and products is also an important factor in shaping teenagers’ consumptive behavior. This research highlights the complexity of the phenomenon of adolescent consumptive behavior and emphasizes the importance of developing a holistic approach in managing its impact.